Pencapaian Kompetensi Dasar Materi Musik Kelas XI SMAN 4 Padang - Muhammad Zaki El Hanif; Tulus Handra Kadir (FBS Universitas Negeri Padang, 2021)
This study aims to find out and describe the process of achieving the basic competencies of grade XI music materials at SMA N 4 Padang. The type of research used is qualitative research with descriptive methods of analysis. The main instrument in this study was the researchers themselves. Data collection techniques are conducted by means of observations, interviews, library studies and documentation. The steps of analyzing data are collecting data, describing data and concluding data. The results showed that the achievement of basic competencies of cultural arts subjects of music material class XI IS 1 as reflected in the implementation of the learning, has not been achieved as planned in the learning planning. The reason the researchers say is still not achieved, because in the implementation of learning by teachers focused on